The portuguese-speaking World between West and East : China, Lusophone countries and the geopolitics the 21st century - Machado, Pamela (2022)
With the acceleration of globalisation and the waning influence of Western directives in the international system, the two first decades of the 21st century were marked by increasing multipolarity and the rise of forms of diplomacy among emerging powers. Alternative models have started to arise, culminating in more initiatives of 'South-South Cooperation' (SSC), a new development framework based on shared experiences among countries in the Global South. This changing order is an opportunity to study and reinvent the current paradigm. In this context, the Portuguese language has an interesting role in the transformation of global politics, even if it has often been overlooked.. While countries of the Portuguese-speaking Global South used to be under stronger Western influence, the rise of new powers, especially China, has created new opportunities and new alliances. This dissertation sought to map and understand Chinese presence in the Lusophone world of the Global South, using the case studies of Lusophone Africa, in the context of rising geopolitical powers. Through exploratory research and review of literature, the purpose was to answer two main questions: firstly, seeking to understand Chinese multilateralism and foreign policy towards the Portuguese-speaking world, looking at the case study of Angola; and secondly, looking at the experiences of Portuguese- speaking countries in the Global South and moving from theory into practical examples, it sought to understand democratic development and map some of the most pressing problems with the intent of finding more sustainable and democratically sound solutions